Comparison of Pain with Systemic NSAIDs vs Regional Block (Fascia Iliaca) in Cases with Hip Fracture - Ramzan, Muhammad Munib; Farrukh, Kalsoom; Ikram, Adeela (Biological and Clinical Sciences Research Journal, 2025)
Hip fractures are a growing global health concern, particularly in elderly populations, and effective pain management is crucial to improve outcomes. While systemic nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used, regional techniques such as the fascia iliaca block (FIB) may provide superior analgesia with fewer systemic adverse effects. This study aimed to compare the efficacy of systemic ketorolac with FIB in managing postoperative pain in patients with hip fractures. Methods: A randomized controlled trial was conducted in the Department of Anesthesia at the National Hospital and Medical Centre, Lahore, from January 2024 to January 2025. A total of 80 patients aged 30–70 years with hip fractures were randomized into two groups: Group A received intravenous ketorolac (30 mg twice daily), while Group B received FIB with 0.25% bupivacaine. The primary outcome was postoperative pain intensity at two hours, assessed using the Visual Analogue Scale (VAS). Demographic and clinical variables were recorded, and data were analyzed using SPSS v24.0 with a significance threshold of p ≤ 0.05. Results: Patients in the FIB group reported significantly lower postoperative pain scores (3.65 ± 1.83) compared with the ketorolac group (6.75 ± 0.49; p < 0.001). Subgroup analyses consistently showed lower pain scores with FIB across various demographic characteristics, including age, gender, BMI, ASA status, fracture duration, and surgical duration. FIB maintained effective analgesia even in prolonged procedures (>2 hours). No major complications were reported. Conclusion: The fascia iliaca block provided significantly superior pain relief compared to systemic ketorolac in patients with hip fractures. Its efficacy across diverse subgroups highlights its value as a safer and more effective analgesic strategy, particularly in resource-limited settings. Wider adoption of FIB could improve postoperative outcomes, reduce reliance on systemic NSAIDs, and enhance recovery in elderly patients with hip fractures.